(untitled) (Samriddhi Journal of Development Studies, 2024)
Sustainable menstrual health is vital for environmental and personal well-being but remains under-prioritized in Nepal. This study assesses awareness and willingness to adopt sustainable menstrual products among bachelor’s level women students in Kathmandu Metropolitan City (KMC), using the Theory of Planned Behavior. A survey was conducted among 150 students from six different institutions (three private and three community). Findings suggested that although there is a high level of awareness regarding sustainable menstrual products, there is also a comparatively high level of desire to adopt them. While a significant relationship was found between awareness and willingness to adopt sustainable menstrual products, awareness alone does not fully explain the decision to switch. Factors such as accessibility, affordability, cultural beliefs, and social acceptance also play a crucial role in shaping adoption behavior. The study highlights the need for focused interventions, such as awareness campaigns, affordability plans, educational programs and peer engagement to promote sustainable menstrual practices among youth.